Characterization of polymers using the method thermogravimetric - Rodríguez, Ellen; Villegas, Ernesto (Métodos y Materiales, 2010)
Thermogravimetry is a technique that has been used for characterization of materials, especially coal and clays. In recent years, the technique has been extended to other materials. This technique, in addition to other thermal techniques, provides a source of information not only thermal but also chemical. It is important to note that this method does not reveal the chemical composition of the material that is being studying nor identify the thermal changes that are not associated with mass changes such as crystallization or glass transition. Thermogravimetry analyses the mass changes as a result of a variation in temperature or by subjecting a material to a set temperature for a defined period. The mass changes identified can determine under what conditions the materials decompose. The results are expressed graphically by thermograms.